Do guidelines for treating chest disease in children use Cochrane Reviews effectively?: a systematic review - Prayle, A.P.; Cox, Tessy; Smith, Sherie; Rycroft-Malone, Joanne; Thomas, Kim S.; Hughes, Dyfrig A.; Smyth, Alan R. (BMJ Publishing Group, 2017)
Cochrane Reviews summarise best evidence and should inform guidelines. We assessed the use of Cochrane Reviews in the UK guidelines for paediatric respiratory disease. We found 21 guidelines which made 1025 recommendations, of which 96 could be informed by a Cochrane Review. In 38/96 recommendations (40%), some or all of the relevant Cochrane Reviews were not cited. We linked recommendations to 140 Cochrane Reviews. In 37/140 (26%) cases, the guideline recommendation did not fully agree with the Cochrane Review. Guideline developers may fail to use Cochrane Reviews or may make recommendations which are not in line with best evidence.